Leksikalna baza - Gantar, Polona (Jezik in slovstvo, 2009)
In the article we present the compilation of a lexical database for Slovene, which is being undertaken within the framework of the project Communication in Slovene. We first shed light upon the concept from the theoretical point of view, and then position it within the context of concrete results in similar projects for other individual European languages. The dual purpose of the lexical database for Slovene, i.e., for dictionary applications and for natural language processing, determines the description of lexical units from three basic viewpoints: semantic, syntactic and collocational. On the basis of these points of departure we present the construction of the lexical database in terms of content levels and elucidate theoretical reflections on content solutions. Finally we present a tool for processing the lexicogrammatical profile of words, Word Sketch, and describe the programme interface for the production of a lexical database.
Keywords: besedni pomen; Corpus linguistics; korpusna lingvistika; leksikalna podatkovna baza; leksikografija; leksikologija; lexicography; lexicology; Slovene; slovenščina